THE ROLE OF THE INVESTMENT AND INNOVATION POTENTIAL OF ENTERPRISES IN ATTRACTING FOREIGN INVESTMENTS TO THE COUNTRY’S ECONOMY - Gafurova Umida Fatikhovna (American Journals, 2023)
This article examines the essence of investment attractiveness, the opinions of economists about increasing investment attractiveness in attracting foreign direct investments. Also, the factors influencing the investment attractiveness of our country were analyzed, and internationally recognized indicators assessing the country’s business environment and the level of investment risks were discussed. Scientific conclusions and recommendations on increasing investment attractiveness in attracting foreign direct investments have been formulated.
Keywords: investment, investment climate, investment attractiveness, Beri – (Business Environment Risk Intelligence) index, indicator, foreign direct investment, recipient, donor, business, segment, progression, investment potential.